Endothelial lipase 584C/T gene polymorphism in coronary artery disease in Elazig population: a pilot study - Susam, Solmaz; İlhan, Necip; İlhan, Nevin; Akbulut, Mehmet (My University, 2018)
Objectives: Coronary artery disease (CAD) is one of the major causes of death in the world. It can be a result of environmentalor genetic factors. A single nucleotide polymorphism (SNP) is a variation of 1 nucleotide sequence in anyregion of the genome, which may cause susceptibility to the disease. Therefore, SNPs have been proposed as idealmarkers in disease association studies. Endothelial lipase (EL) is a protein of the triglyceride lipase family that plays animportant role in high-density lipoprotein (HDL) metabolism. The EL gene has a common 584C/T polymorphism, but itis unclear whether this polymorphism is associated with HDL-cholesterol levels or CAD. The purpose of this study wasto investigate the relationship between the EL 584C/T gene polymorphism, HDL level, and the risk of CAD in residentsof Elazig province.Methods: The population of this study consisted of 78 patients with angiographically confirmed CAD and 81 healthycontrols. Genotyping for the 584C/T polymorphism was performed using the polymerase chain reaction-restrictionfragment length polymorphism technique.Results: The frequency of the CT, CC, and TT genotypes was 40.74%, 56.8%, and 2.46%, respectively, in the controlgroup, and 66.67%, 30.37%, and 2.56%, respectively, in the CAD group. The Hardy-Weinberg value was p<0.05 for thecontrol group and p>0.05 for the CAD group. No significant association was found between the 584C/T variant and HDLlevel. The T allele frequency was higher in the CAD group than among the controls.Conclusion: It was concluded that the T allele was associated with a risk of CAD in Elazig province, independent of theHDL-cholesterol level.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Kalp ve Kalp Damar Sistemi